CONCENTRAÇÃO MUNDIAL DE EXPORTAÇÕES DE PRODUTOS FLORESTAIS MADEIREIROS/World’s concentration of timber forest products exports - Furtado Santos, Helenice; Lopes da Silva, Márcio; Silva Soares, Naisy; Coelho Junior, Luiz Moreira (Informe GEPEC, 2024)
The world’s economy has undergone several changes and crises that may have altered the dynamics and structure of the forestry market after 2008. Thus, the objective of this study was to measure the concentration of the international market of the main forest products between 2009 and 2018. We used the Concentration Ratio [CR(k)], Hirschman-Herfindahl Index (HHI), Theil Entropy Index (E) and Gini Coefficient (G) to evaluate the forest products concentration. The results showed that American and Asian countries have risen and taken positions of major forest products exporters to European markets over the years. The main exported product was “Paper and cardboard”, followed by “Lumber”, “Pulp”, “Wooden panels”, “Wood for industrial purposes” and “Wood for Energy”. Brazil’s global share stood out in the pulp and paper segments. The forest products market concentration was classified as low for CR4, moderately low for CR8, unconcentrated and highly competitive for HHI and Entropy indices. Furthermore, the market was classified with inequality from very strong to absolute using the Gini index indicating that exports come from a small number of nations. In general, there is competitiveness among exporting countries, which favors the development of the sector and the entry of new players into the timber forestry trade. The dynamics and implications presented are essential for formulating strategic decisions, policies and investments that will determine the sector’s development. Resumo: A economia mundial passou por diversas mudanças e crises que podem ter alterado a dinâmica e a estrutura do mercado florestal após 2008. Assim, o objetivo deste estudo foi medir a concentração do mercado internacional dos principais produtos florestais entre 2009 e 2018. Utilizamos a Razão de Concentração [CR(k)], o Índice de Hirschman-Herfindahl (HHI), o Índice de Entropia de Theil (E) e o Coeficiente de Gini (G) para avaliar a concentração dos produtos florestais. Os resultados mostraram que os países americanos e asiáticos cresceram e assumiram posições de grandes exportadores de produtos florestais para os mercados europeus ao longo dos anos. O principal produto exportado foi "Papel e papelão", seguido por "Madeira serrada", "Celulose", "Painéis de madeira", "Madeira para fins industriais" e "Energia". A participação global do Brasil se destacou nos segmentos de papel e celulose. A concentração do mercado de produtos florestais foi classificada como baixa para CR4, moderadamente baixa para CR8, não concentrada e altamente competitiva para os índices HHI e Entropia. Além disso, o mercado foi classificado com desigualdade de muito forte a absoluta usando o índice de Gini, indicando que as exportações vêm de um pequeno número de nações. De forma geral, e existe competitividade entre os países exportadores, o que favorece o desenvolvimento do sector e a entrada de novos players no comércio florestal madeireiro. As dinâmicas e implicações apresentadas são essenciais para a formulação de decisões estratégicas, políticas e investimentos determinantes para o desenvolvimento do sector.